INTRODUCTION OF INCLUSIVE EDUCATION - HUMAN ATTENTION AND THE FOUNDATION OF SOCIAL PROTECTION - Jo'rayeva Gulshoda,; Mirahmedova Dilafruz, (Zeta Repository, 2023)
Today's education system aims to identify young people as munoib heirs for the next day. This article describes how it is a time-consuming requirement for students with disabilities to be taught in the same way as healthy students.